The Art of Storytelling in Tablighi Jamaat: Emotional Engagement as a Strategy for Societal Transformation in the Islamic Revivalist Movement - Ali, Kausar; Minxing, Huang (Journal of Al-Tamaddun, 2025)
This research article seeks to explore the emotional impact of storytelling within the Islamic revivalist movement known as the Tablighi Jamaat. The Tablighi Jamaat is a contemporary Islamic revivalist movement focused on spreading Islam and encouraging Muslims worldwide to adopt a more devout practice of their faith. This article explores how the storytelling approach of Tablighi Jamaat taps into human emotions through the sharing of personal experiences. Through a combination of qualitative and quantitative research method, this research article demonstrates how Tablighi campaigners use these powerful stories to motivate individual Muslims to become more devoted and practicing followers of their religion. The article further argues that human emotions play a crucial role in individual mobilization, identity formation, and socio-religious unity by creating emotional ties to Islamic beliefs, practices, and other religious rituals. The article also suggests that these compelling stories stir a blend of positive and negative human emotions in ordinary Muslims, encouraging them to embrace the dawat and Islamization efforts of the Tablighi Movement.